Influence of Voxelotor–hemoglobin complexes in the estimation of hemoglobin S levels by the current standard of care laboratory evaluation techniques - Alkindi, Salam; Al Subhi, Ahmed; Ali, Abubakr E. H.; Pathare, Anil V. (Frontiers in Medicine, 2023)
Background Sickle cell disease is an inherited disorder characterized by the presence of sickle hemoglobin (HbS). The process of Hb molecule polymerization is a pivotal step in the sickling process. Voxelotor, a recently approved novel therapeutic agent, is known to interfere with polymerization. We aim to study the impact of Voxelotor on Hb variants analysis using high performance liquid chromatography (HPLC). Material and methods We are reporting the impact of Voxelotor on Hb variants analysis using HPLC after an informed consent and medical research committee approval. Data was collected from eight patients who are enrolled in the GBT440-034OL study using electronic medical records, to evaluate the Hb levels, hemolytic markers and the clinical response. Results Our patients were well-balanced for gender, with a mean age of 31.1 years (19–50). Six patients showed a significant improvement in the Hb level, with reduced reticulocytes, bilirubin, LDH and an improved clinical outcome. Interestingly, these patients showed the appearance of a split band of Hb S and D on HPLC impacting significantly on HbS level. Two patients did not show any improvement on laboratory parameters, and no changes on their HPLC analysis. Conclusions We report here eight patients on Voxelotor therapy, six of which showed improved hemolytic markers and anemia and demonstrated the appearance of HbD peak on the HPLC chromatogram. Therefore, the absence of HbD on HPLC or other laboratory methods for estimating HbS in patients on Voxelotor therapy, gives the clinician a possible hint regarding the patient's compliance with the drug.